Diagnóstico de salud bucodental y factores de riesgo, en el colegio San Vicente Ferrer de la Parroquia Chuquiribamba, del Cantón Loja año 2013. - Masa Pinza, José Francisco (2013)
SUMMARY Oral diseases, including dental caries and periodontal diseases affecting different age groups causing local discomfort with functional and aesthetic impact on overall health. This research was aimed to determine the prevalence of oral diseases and to identify risk factors in Children / College and adolescents "San Vicente Ferrer" in the parish of Canton Chuquiribamba Loja. This study was quantitative, descriptive and transversal study whose population is 195 boys / girls and adolescents, where he performed oral diagnosis and application of oral hygiene surveys and risk factors. The results were: dental caries, 98.9% and 96.3% gingival inflammation are the most prevalent diseases, influenced by improper brushing technique 82.4%, the infrequency of brushing in 43.1% and poor visit 45.7% dentist. After completing the study it can be concluded that there is a high rate of tooth disorder, affecting the health status of the population, affecting the proper development of the individual and the community. As recommended prevention advocacy and oral, the population most at risk. Keywords: Caries, Risk Factors, Gingival Inflammation. Lcda. Paola Elizabeth Seraquive Valarezo. Traductora.